Pengembangan Industri Terakota di Desa Jatipasar Trowulan sebagai Upaya Pelestarian Budaya dan Pemberdayaan Ekonomi Masyarakat - Prihartini Widiyanti; Ikhsan Rosyid Mujahidul Anwari; Usma Nur Dian Rosyidah; Sigit Ari Saputro (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Jatipasar Village in Trowulan is one of the areas that inherited the cultural treasures of Majapahit with cultural heritage in the form of temples, the heritage of terracotta craft motifs. The architectural characteristics of Majapahit became the hallmark of terracotta. Currently in Trowulan alone there are only 5 terracotta craftsmen who exist and 3 from Jatipasar. The terracotta industry has high cultural value and significant economic potential. This community service activity aims to develop the terracotta industry through a one-day seminar workshop method so as to provide knowledge for craftsmen and people who are interested in becoming terracotta craftsmen. The activity was attended by 12 residents consisting of craftsmen and residents with resource person Arif Suharson from ISI Yogyakarta, who provided material on terracotta techniques and marketing. The pre-test and post-test methods were used to measure participants' understanding before and after the activity. The results of this activity showed an increase in participants' understanding of the terracotta industry, as well as contributing to cultural preservation and community economic empowerment.